2021
DOI: 10.3389/fnins.2021.640666
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Optical Coherence Tomography Angiography Detects Retinal Perfusion Changes in Carotid Artery Stenosis

Abstract: BackgroundCarotid artery stenosis (CAS) is a multifaceted disease characterized by possible ocular involvement. Treatment with carotid endarterectomy helps to restore cerebral perfusion, which may prevent ocular and cerebral complications. The main aim was to assess retinal and choroidal vascular perfusion changes before and after endarterectomy in patients affected by CAS.MethodsThe design of the study was prospective and observational, including patients affected by CAS and healthy controls. The follow-up wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…Two studies were removed because their population did not meet the interest, two studies lacked a control group, and two studies lacked sufficiently detailed data. Overall, thirteen studies ( Heßler et al, 2015 ; Sayin et al, 2015 ; Biberoğlu et al, 2017 ; Çakır et al, 2017 ; Wang et al, 2017 ; Lahme et al, 2018 ; Li et al, 2019 ; Biberoglu et al, 2020 ; Dagdelen and Muz, 2021 ; Pierro et al, 2021 ; Incekalan et al, 2022 ; Liu X. et al, 2022 ; Wan et al, 2022 ) were included. The screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were removed because their population did not meet the interest, two studies lacked a control group, and two studies lacked sufficiently detailed data. Overall, thirteen studies ( Heßler et al, 2015 ; Sayin et al, 2015 ; Biberoğlu et al, 2017 ; Çakır et al, 2017 ; Wang et al, 2017 ; Lahme et al, 2018 ; Li et al, 2019 ; Biberoglu et al, 2020 ; Dagdelen and Muz, 2021 ; Pierro et al, 2021 ; Incekalan et al, 2022 ; Liu X. et al, 2022 ; Wan et al, 2022 ) were included. The screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies involving 419 eyes with ICAS and 398 eyes with healthy controls were identified. Eight studies ( Heßler et al, 2015 ; Sayin et al, 2015 ; Çakır et al, 2017 ; Lahme et al, 2018 ; Li et al, 2019 ; Pierro et al, 2021 ; Incekalan et al, 2022 ; Liu X. et al, 2022 ; Wan et al, 2022 ) were prospective, while four ( Biberoğlu et al, 2017 ; Wang et al, 2017 ; Biberoglu et al, 2020 ; Dagdelen and Muz, 2021 ) were retrospective in design. The mean age of patients with ICAS was between 62 and 68 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 , 74 Although no data on the BCAS-induced retinal tissue oxygenation are available, several studies have reported reduced retinal vascular density in subjects with carotid stenosis. 75 78 Indeed, a recent study established a relationship between retinal vascular perfusion and cerebral hemodynamics in subjects with internal carotid artery stenosis. 79 …”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic internal carotid artery stenosis (ICAS) accounts for about 20% cases of cerebral ischemia [ 2 ]. The present diagnostic tools for carotid artery assessment are based on imaging studies, including carotid Doppler ultrasonography, computed tomography, magnetic resonance, or conventional invasive angiography with a use of intravascular ultrasound (IVUS), and optical coherence tomography (OCT) [ 3 , 4 , 5 ]. They display the degree of ICAS, as well as carotid plaque morphology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%